The frog vertebrate dissection guides (Hampshire : University of Portsmouth)
Explores the functional anatomy af an animal commonly used in practical biology
System requirements: Windows 95/98/NT4, directX software component with Windows, 16 Mb RAM (32Mb recommended), 800 X 600 display resolution, 16 bit sound card
Keywords: Frogs; Frogs -- Anatomy